Evaluation and clinical implications of interactions between compound Danshen dropping pill and warfarin associated with the epoxide hydrolase gene - Chen, Xixi; Zuo, Xurui; Zhao, Yingqiang; Huang, Yuhong; Lv, Chunxiao (Frontiers in Pharmacology, 2023)
In clinical practice, warfarin is often combined with Compound Danshen dripping pill (CDDP) for the treatment of cardiovascular diseases. However, warfarin has a narrow therapeutic index, wide interindividual variability (genetic and non-genetic factors), and is susceptible to drug-drug interactions. Our previous study indicated that CDDP might interact with warfarin in individuals with the epoxide hydrolase gene (EPHX1; single-nucleotide polymorphism: rs2292566) A/A subtype. We sought to clarify the interaction between CDDP and warfarin associated with EPHX1 in a comprehensive and accurate manner. Here, EPHX1 A and EPHX1 G cell lines were established. Expression of microsomal epoxide hydrolase (mEH), vitamin K epoxide reductase (VKOR), and vitamin K-dependent clotting factors (FII, FVII, FIX, FX) was measured by western blotting upon incubation with CDDP and warfarin. mEH activity was evaluated by measuring the transformation of epoxyeicosatrienoic acids into dihydroxyeicosatrienoic acids. Then, healthy volunteers (HVs) with the EPHX1 A/A genotype were recruited and administered warfarin and CDDP to investigate the pharmacokinetics and pharmacodynamics of warfarin. CDDP combined with warfarin could decrease expression of mEH and VKOR, and increase protein expression of FII, FVII, FIX, and FX, in EPHX1 A cells. CDDP could slightly influence the pharmacokinetics/pharmacodynamics of warfarin in HVs with the EPHX1 A/A genotype. Rational combination of CDDP and warfarin was safe with no risk of bleeding, but the therapeutic management is also needed. The clinical study is posted in the China Clinical Trial Registry (ChiCTR190002434).